The Relationship Of Vulva Hygiene Behavior With Pruritus Vulvae Events When Menstruate In Adolescent Princess In Kalanganyar Village - Khusnul Nikmah; Maghfirotun Ni'mah (Universitas STRADA Indonesia, 2020)
This study is analytical in nature because it tries to determine the incidence of Pruritus vulvae. The data were analyzed using the chi square test. The population in this study were all young women from the Kalanganyar village, Lamongan Regency. The sample in this study were 30 female teenagers in Kalanganyar Village RT 04 and RT 05. The results showed that young women who had personal hygine behavior during menstruation were not good. Most of them experienced pruritus vulvae as many as 25 (85%) of respondents. The results of the chi square test showed that the value of p = 0.004 means that there is a relationship between personal hygiene behavior and the incidence of pruritus vulvae during menstruation in young women in the village of circles. Poor personal hygiene behavior can affect the incidence of pruritus vulvae